Optimisation Of In Vitro Intracellular Antileishmanial Assay And Evaluation Of Senna Spectabilis (DC.) H. S. Irwin Barneby Methanolic Leaf Extract And Its Constituents Against Leishmania Major Using Bioassay-Guided Isolation Approach - Sain, Amyra Amat (2016)
Leishmaniasis affects millions of people each year. Alternative approaches are needed because majority of those infected live in countries which could not afford financially in marketdriven dmg discovery. Current treatments faced side effects such as cardiotoxicity and nephrotoxocity, and require a long course of treatment which may develop resistance of parasites. Senna spp have been known for antiparasitic characteristics and recently reported for its antileishmanial activity against extracellular L. major. There are two assays used to test in vitro antileishmanial activities in this work which are leishmanicidal and intracellular amastigote assays. The main aim of this study was to establish and optimise the in vitro antileishmanial intracellular amastigote assay, while maintained the leishmanicidal assay as the preliminary screening tool to obtain the hits. The optimised intracellular amastigote assay was then used to evaluate antileishmanial activities of active constituents from a medicinal plant, S. spectabilis via bioassay-guided isolation approach. At first, the evaluation of antileishmanial activity of methanolic leaves extract from S. spectabilis were carried out using the leishmanicidal assay which was also known as in vitro extracellular promastigote assay with promastigote stage of L. major as the parasite. This assay was done based on Alamar Blue® assay with little modification. As a result, ethyl acetate (CS-EA) extract of the plant was found to be active with IC50 = 70.29 ± 0.38 1-ig/mL and was further fractionated. For further antileishmanial evaluation of fractions, the in vitro intracellular amastigote assay was used, and this assay was first to be established in Malaysia. In this assay, amastigote stage of L. major was used to infect THP-1 cell (macrophage) stably before treating the infection with substituents from S. spectabilis in 16-well chamber slide format. The seeding number of THP-1 cells was optimized at 2.0x 104 cells/well and ratio of infection was optimised at 5: 1 of parasite to host. The assay was then validated using Amp-Bas the standard drug with EC50 = 0.437 ± 1.06 11M.